Laboratory inquiry in chemistry - Bauer, Richard C. (Thomson / South-Western, 2005)
LABORATORY INQUIRY IN CHEMISTRY teaches you the skills you need to easily complete your laboratory investigations. Each investigation begins with a scenario that puts a real-life spin on the problem at hand, provides you with a sense of why the project is relevant, and creates a scenario that is comparable to what chemists face in the real world. Completing experiments is easy with a list of goals, materials, reagents, guidelines, and hints found at the beginning of each investigation.